Behavioral profile, lifestyle and social skills in Portuguese adolescents - Clarisse Magalhães (BMC Public Health, 2021)
Abstract Background Seventy percent of premature deaths in adults are due to behaviors initiated during adolescence. Therefore, it is essential to promote individual and social behaviors that educate adolescents in the ability to make healthy choices. Accordingly, the main goals of this study were to characterize Lifestyles and Social Skills, as well as identify homogeneous subgroups, in a sample of Portuguese adolescents. Methods A cross-sectional study was conducted, including 1008 adolescents attending the 7th to the 9th grades of five middle schools from the Tâmega and Sousa regions of Portugal, and using the My Lifestyle Questionnaire and the Social Skills Inventory. To establish a profile of the participants, a Cluster Analysis (K-means) was performed, and the Jaccard coefficient was used to assess the stability of the solution found. Results From the total sample, 556 adolescents with a mean age of 13.43 years (SD = 1.1) were included in the analysis. The majority of the sample presented a healthy lifestyle (72.26%) and 50.7% of the adolescents had a highly elaborated repertoire of Social Skills. Moreover, three clusters were found. Cluster 1 (n = 92) showed a less elaborate repertoire of Social Skills and was designated as the “Adjusted”. Cluster 2 (n = 115) comprised adolescents with a good repertoire of Social Skills and was named the “Sociable”. Cluster 3 (n = 258) was composed of adolescents with a highly elaborate repertoire of Social Skills and the best Lifestyle indicators and was named the “Healthy”. Conclusions The group of adolescents in the cluster called the “Sociable” needs to be included in health education and Social Skills programs. Nutrition and Monitored Safety behaviors reveal low values and, therefore, present a greater need for awareness, sensitization, and intervention in the school context. For this reason, the promotion of a healthy lifestyle should be part of the academic curriculum and transversal to all academic disciplines.